Analisis Dampak Instrumen Kebijakan Moneter Terhadap Stabilitas Perekonomian di Indonesia - Fauzi Rahmadani; Hasdi Aimon (Jurnal Kajian Ekonomi dan Pembangunan, 2022)
The purpose of this study is to determine how the influence of monetary policy instruments on economic stability in Indonesia. Monetary policy instruments as exogenous variables are policies in the money supply M2 (X1) and Bank Indonesia interest rates (X2) while indicators of economic stability as endogenous variables can be seen from price stability (Y1) and exchange rate stability (Y2). This research is descriptive and associative research. The data used in this study is monthly secondary data from January 2001 to December 2020 which was collected through documentation from the relevant agencies. The data analysis used in this research is descriptive analysis and inductive analysis. In the inductive analysis there are several tests, namely (1) Stationarity Test; (2) Cointegration Test; (3) Multiple Linear Regression Test and Error Correction Model (ECM); (4) Classical Assumption Test; (5) T test and F test. The results of this study is: (1) in the long term and short term the money supply M2 has a negative effect on price stability in Indonesia; (2) Bank Indonesia interest rates in the long term and short term have a positive influence on price stability in Indonesia; (3) in the long term and short term The money supply M2 has a positive influence on the stability of the exchange rate in Indonesia; (4) Bank Indonesia interest rates in the long term and short term have a positive influence on exchange rate stability in Indonesia.